2013
DOI: 10.1371/journal.pone.0076589
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Vaginal Pathogenic Community and Bacterial Vaginosis in Chinese Reproductive-Age Women

Abstract: BackgroundBacterial vaginosis (BV) is one of the most common urogenital infections among women of reproductive age that represents shifts in microbiota from Lactobacillus spp. to diverse anaerobes. The aim of our study was to evalute the diagnostic values of Gardnerella, Atopobium, Eggerthella, Megasphaera typeI, Leptotrichia/Sneathia and Prevotella, defined as a vaginal pathogenic community for BV and their associations with vaginal pH and Nugent scores.Methods and FindingsWe investigated the vaginal pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(45 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, Fusobacterium is the only butyrogenic genus which showed twofold higher occurrence in all the patients suffering from CRC (95 samples) and IBD (101 samples). Also, although butyrogenic genus Megasphaera was not observed in the guts of the subjects considered in this study, it has been reported to have higher abundance in many diseased conditions (Bajaj et al, 2012; Ling et al, 2013; Chiu et al, 2014). The presence of butyrogenic bacteria in the guts of diseased individuals calls for an in-depth comparison of various butyrate production pathways in likely pathogens and commensals.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, Fusobacterium is the only butyrogenic genus which showed twofold higher occurrence in all the patients suffering from CRC (95 samples) and IBD (101 samples). Also, although butyrogenic genus Megasphaera was not observed in the guts of the subjects considered in this study, it has been reported to have higher abundance in many diseased conditions (Bajaj et al, 2012; Ling et al, 2013; Chiu et al, 2014). The presence of butyrogenic bacteria in the guts of diseased individuals calls for an in-depth comparison of various butyrate production pathways in likely pathogens and commensals.…”
Section: Resultsmentioning
confidence: 53%
“…Similarly, Megasphaera elsdenii , another butyrogenic organism, was found to utilize only 4Ab pathway. The abundance of this genus has been reported to increase in case of diseased conditions like obesity, hepatic encephalopathy and bacterial vaginosis (Bajaj et al, 2012; Ling et al, 2013; Chiu et al, 2014). Thus, the results of the present study indicate possible correlation between butyrogenic gut bacteria that belong to genera which show higher abundance in diseased condition and lack of the pyruvate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Two important areas of consensus emerged. First, almost all women carry vaginal lactobacilli regardless of their BV status by Nugent or Amsel criteria [19], [20], [22], [23], [25], [26], [33], [37]–[42], [45], [47], [48], [54], [59], [60], [62], [63], [73], [76], [80] but L. crispatus is predominantly found in BV-negative women [20], [22], [23], [25], [32], [33], [37], [38], [40], [42], [48], [50], [54], [59], [60], [62], [63], [65], [73], [75], [76], [80] whereas L. iners (and to a lesser extent L. gasseri ) is also found in women with intermediate microbiota or BV [21], [23], [25], [33], [37], [38], [40]–[42], [47], [50], [54], [59], [60], [62], [63], [65], [73], [76], …”
Section: Resultsmentioning
confidence: 99%
“…Vice versa, increasing abundance of lactobacilli is consistently associated with a lower vaginal pH [30], [40], [67], [80] and Nugent score [80]. Associations with the other Amsel criteria have been less well studied, but one study found that only the Leptotrichia and Eggerthella genera were associated with all four Amsel criteria [60].…”
Section: Resultsmentioning
confidence: 99%
“…isolated. Ling et al, (2013) indicated that vaginal pathogenic bacteria such as Gardenerella vaginalis, Prevotella spp., Atopium vaginae, Eggerthella and Leptotrichia/Sneathia are highly predictable for BV, with excellent diagnostic accuracy. Unfortunately, in the present work, we failed to isolated Gardenerella vaginalis by the routine culture methods followed in our laboratories.…”
Section: Diagnostic Performance Of Vaginal Swab Culture Compared To Nmentioning
confidence: 99%